Nutrient depletion and phytoplankton shifts driven by the Pearl River plume in the Taiwan Strait - Tong, Zhuyin; Wang, Changyun; Lin, Lizhen; Ma, Lingqi; Huang, Bangqin (Frontiers in Marine Science, 2024)
The intrusion of the Pearl River plume into the Taiwan Strait provides a unique case study that challenges traditional assumptions about the impacts of nutrient-rich river plumes on coastal phytoplankton communities. In this study, we conducted a detailed analysis of nutrient dynamics and phytoplankton composition within the Taiwan Strait, focusing on the effects of the Pearl River plume. Our findings reveal significant nutrient depletion, particularly of nitrogen, in the surface waters as the plume extends seaward, resulting in nitrogen limitation and a marked reduction in phytoplankton biomass. Vertical stratification within the Taiwan Strait creates distinct ecological niches, with the mid-layer supporting a deep chlorophyll maximum and the surface layer becoming dominated by the picophytoplankton Synechococcus. This shift from diatom-dominated communities to Synechococcus dominance has far-reaching implications for carbon cycling and food web dynamics in the region. Our results suggest that the Pearl River plume’s influence on the Taiwan Strait represents a departure from the typical nutrient enrichment associated with river plumes, highlighting the complexity of coastal biogeochemical processes.